Pendampingan Kelompok PKK Melalui Penyuluhan Optimalisasi Pola Hidup Bersih Dan Sehat Untuk Kader PAUD di Desa Sanca Kecamatan Ciater Kabupaten Subang - Andre Ariesmansyah; Nina Kurniasih; Nur Fitriani Arningsih; Danti Nuracti (Jurnal Pengabdian Masyarakat Formosa, 2022)
PAUD has an important role in improving the quality of early childhood education services, because it is considered a symbol in the national movement for quality early childhood education. Clean, healthy and well-nourished behavior is one of the main ways in establishing a foundation that makes children healthy and not easily sick. Four healthy five perfect is a term that is very often used for children, it is related to nutrition for children. Lack of knowledge and lack of awareness of the importance of implementing PHBS. Parents who smoke in the house, the number of piles of garbage that become a nest of disease, Taking hygiene and health problems trivially. The expected solution is to increase knowledge and understanding of Clean and Healthy Behavior (PHBS) and Balanced Nutrition for children in PAUD, provide socialization by inviting expert resource persons to explain about Healthy Living Behavior and Balanced Nutrition for children. So that partners can implement a healthy life in the PAUD environment. The approach method used to overcome the problems faced by partners is through outreach activities, training or counseling, and consultation. An active participatory approach that is carried out between the implementing team and partners on an ongoing basis and plays an active role in providing assistance and coaching. Based on the results of the pretest, cadres' knowledge of PHBS during the pandemic had an average value of 56.6 with the topic of knowledge about PHBS and the importance of balanced nutrition, the posttest results showed an increase in knowledge to 63 from the previous 56.6. Nearly 85% of participants in the PHBS material and the importance of balanced nutrition for health have very good knowledge.